PERAN GURU IPA DALAM PENGEMBANGAN BAKAT AKADEMIK SISWA - Harefa, Darmawan; Sarumaha, Murnihati; Fau, Amaano; Ziraluo, Yan Piter Basman; Lase, Indah Permata Sari; Telaumbanua, Kaminudin; Bali, Selfi Yanti; Telaumbanua, Tatema; Novialdi, Andrian (Jurnal Ilmiah Aquinas, 2022)
This research motivated by the problem academic talent, especially in science-physics subjects, because many students do not achieve minimum mastery in science-physics subjects. Research sub-focus 1) The performance of science-physics teachers at the BNKP Telukdalam Christian Private Junior High School. 2) The academic talent of the seventh grade physics subject. The type of research used is qualitative research with a phenomenological approach. The results showed that 1) The performance of the science-physics teachers was good, where the Guidance and Counseling teachers carried out their duties well according to the function of Guidance and Counseling services. 2) Grade VII students have IPA-Physics academic talent, where students try to solve difficult problems by asking the IPA-Physics subject teacher, and looking for reference sources on the internet that have the same IPA-physics questions. The conclusion of the research on the role of science-physics teachers in developing students' science academic talent by providing knowledge about talent, teachers providing insight into knowledge about their talents, it can open up students' views about their talents more broadly.